Anthropological considerations of production, exchange, vending and tourism - Wood, Donald C. (Research in economic anthropology, 2017)
Volume 37 of REA features eleven original articles organized in four different sections, each focusing on a specific, popular and significant theme in economic anthropology: production, exchange, vending, and tourism.